Conditions and the effects of intervention and entry before the administrative courts - Hamid Tayes, Riad (International Journal of Psychosocial Rehabilitation, 2023)
Through this thesis, I tried to know the development witnessed by the Civil Procedures Law, within the framework of the litigation issue in the administrative matter, which means the total procedures followed before the courts since the filing of the case until the issuance of the ruling.